Pengaruh PBL Berorientasi One Stay Another Stray terhadap Keterampilan Komunikasi Peserta Didik: Penelitian - Dwi Putri Nur Annisa; Muhyiatul Fadilah; Fitri Arsih; Ria Anggriyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of the Fun Learning-oriented Problem Based Learning (PBL) model with the One Stay Another Stray (OSAS) approach on students' written communication skills on the material of environmental change and conservation. The research was conducted in class XB 2 SMAIT Dar El Iman using a pre-experiment design in the form of a one-group pretest-posttest. The sample was selected using purposive sampling technique. Data obtained from pretest and posttest results were analyzed using the Shapiro-Wilk normality test, Levene homogeneity test, Wilcoxon Signed-Rank Test hypothesis test, and N-Gain test. The results showed a significant increase in students' written communication skills after applying the Fun Learning OSAS-oriented PBL model. The average pretest score increased from 64 to 81 on the posttest, with a hypothesis test significance value of 0,000 (<0,05), which indicates a positive effect of the model on communication skills. The N-Gain test showed an average increase of 0,52 which is classified as moderate. All indicators of written communication, namely explaining objects, presenting data in tabular form, and making pictures or diagrams have increased.